Pengaruh Model Pembelajaran Inkuiri Terbimbing terhadap Hasil Belajar Peserta Didik SMPN 2 Kupang - Merliana Gisela; Hildegadis Missa; Getrudis Wilhelmina Nau (Program Studi Pendidikan Biologi Universitas Katolik Widya Mandira, 2025)
The problem in this study is the low learning outcomes of students in science learning, which is still dominated by teacher-centered methods. This research aims to determine the effect of applying the guided inquiry learning model on the learning outcomes of eighth-grade students at SMPN 2 Kupang on the topic of the human excretory system. The study employed a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of class VIII D (experimental, n=32) using the guided inquiry model and class VIII E (control, n=32) using direct instruction. Learning outcomes data were collected through pretest and posttest, and analyzed using descriptive statistics, normality test, homogeneity test, and ANCOVA. The results showed that the average N-Gain of the experimental class was 0.63 (high category) and the control class was 0.50 (medium category). The ANCOVA test obtained a significance value of 0.002 < 0.05, indicating a significant effect of the guided inquiry model on learning outcomes. The study concludes that guided inquiry learning can significantly improve student learning outcomes in the human excretory system topic.